Can eicosapentaenoic acid maintain the original ribavirin dose or affect the response during the treatment course of chronic hepatitis C virus (HCV) patients? - Morsy, Khairy H; Zaghloul, Amr; Mahmoud, Magdy (Turkish Journal of Gastroenterology, 2016)
Abstract Background/Aims: Combination therapy with peginterferon (PEG-IFN) and ribavirin (RBV) has been recommended as a standard therapy for patients with chronic hepatitis C virus (HCV). Our aim was to evaluate the efficacy of eicosapentaenoic acid (EPA) against RBV-associated hemolytic anemia. Materials and Methods: Two hundred and forty HCV patients included in the study were randomized to either the EPA group (n=120) or non-EPA group (n=120), and they received combination therapy with or without EPA. We compare changes in hemoglobin levels with RBV dose reduction rate in each group as well as treatment response. Results: Of 120 patients randomized to receive combination therapy with EPA, 15/86 (17.5%) patients required RBV dose reduction, whereas 71/86 (82.5%) patients did not require RBV dose reduction; in the non-EPA group, 22/80 (27.5%) patients required RBV dose reduction and 58/80 (72.5%) patients did not require RBV dose reduction. There was no significant difference between the two groups in the rates of virologic response. Conclusion: EPA can decrease the rate of RBV dose reduction and RBV-induced hemolysis during the course of combination treatment. Further trials are required to investigate the role of EPA in the current regimens of HCV treatment that include ribavirin.